Metacercarial Infection of Wild Nile Tilapia (Oreochromis niloticus) from Brazil - Hudson A. Pinto; Vitor L. T. Mati; Alan L. Melo (The Scientific World Journal)
Fingerlings of Oreochromis niloticus collected in an artificial urban lake from Belo Horizonte, Minas Gerais, Brazil, were evaluated for natural infection with trematodes. Morphological taxonomic identification of four fluke species was performed in O. niloticus examined, and the total prevalence of metacercariae was 60.7% (37/61). Centrocestus formosanus, a heterophyid found in the gills, was the species with the highest prevalence and mean intensity of infection (31.1% and 3.42 (1–42), resp.), followed by the diplostomid Austrodiplostomum compactum (29.5% and 1.27 (1-2)) recovered from the eyes. Metacercariae of Drepanocephalus sp. and Ribeiroia sp., both found in the oral cavity of the fish, were verified at low prevalences (8.2% and 1.6%, resp.) and intensities of infection (only one metacercaria of each of these species per fish). These species of trematodes are reported for the first time in O. niloticus from South America. The potential of occurrence of these parasites in tilapia farming and the control strategies are briefly discussed.